Adherence to IPT among HIV adolescents aged 11 to 19 years at Kisenyi health center IV, Kampala district. A cross-sectional study. - Bukenya, Bonny; Namujjuzi, Lilian; Nalubega, Jane Frank; Nansereko, Hasifa; Naggulu Prosperia, Immaculate (Student’s Journal of Health Research Africa, 2025)
Background Adherence to Isoniazid Preventive Therapy (IPT) is crucial for HIV-positive adolescents to prevent tuberculosis (TB). When forfeited, it poses severe health risks. This study thus aimed at exploring the factors influencing adherence to IPT among HIV-positive adolescents aged 11 to 19 years, focusing on socioeconomic, individual, and health facility-related factors. Methodology A descriptive cross-sectional study design was employed, involving 30 HIV-positive adolescents selected through simple random sampling. Data was collected using structured questionnaires translated into the local language for better comprehension. The collected data were analyzed using Microsoft Excel, and the results were presented in tables and figures. Results The study involved more females (20, 67%) than males (10, 33%), with the majority (70%) aged between 17 and 19 years and not living with their parents or guardians (21, 70%). Findings revealed significant socioeconomic challenges, with 56% of respondents reporting struggles to afford basic needs, which influenced adherence to IPT. Most participants (60%) found it difficult to access the health center for appointments. On individual factors, 70% of adolescents had a limited understanding of IPT benefits, while 80% expressed concern about potential side effects, negatively influencing adherence. Additionally, 70% had stigma associated with taking IPT, leading to treatment avoidance. Positively, 60% of respondents had stable housing, and 80% felt confident in managing IPT as part of their lives. Regarding health facility factors, 70% reported long wait time, while 80% noted consistent availability of IPT medication, which supported adherence. Conclusion Adherence to IPT among HIV-positive adolescents at Kisenyi Health Center IV is influenced by various factors such as low socio-economic status and long wait hours, which impede access to health care. Recommendation Implementation of targeted educational programs, enhancing access to healthcare services, training staff for supportive interactions, and developing reminder systems to help adolescents manage their medication routines.